The importance of Algerian sports media in developing the sports professionalism system in Algeria. - zouaoui, Abdelouahab (sports creativity, 2025)
The history of media dates back to the beginning of humankind. Humans are social by nature, instinctively seeking to exchange information and ideas with others. However, the means of exchange have changed throughout history. Media is a fundamental component of the social structure, and given the importance of sports in society, sports media is a key element in conveying sporting life objectively and comprehensively. The development of media technologies, especially in the sports field, is driven by the dynamism of sports within society and the diverse uses of sports by its members. Sports activity is essential for the intellectual, mental, and educational development of individuals, and sports media is a necessity dictated by the desires and needs of individuals to acquire knowledge, develop sporting ideas, and exchange them with others. Sports derive their popularity from the massive coverage they receive thanks to media and communication. These media have dissolved boundaries and blended cultures. The popularity of sports has even transcended affiliations and prejudices. Returning to the academic sphere, the phenomenon of sports is often studied in terms of social levels and the sociological effects that sports may produce in society, or the technical dimension of sports in its relationship to the human body as the source of all movement. But this study extends to another equally important dimension: the sports media dimension. The legal framework aims to develop the sports system in general and the professional sports system in particular, which makes and confirms the practice of sports as an organized activity in which all rights are preserved. The study addresses the relationship between sports media and sports in its professional sense, which has become a social, cultural, economic, and political phenomenon in our present era, attracting the attention of all segments of society at a time when sports media consumption of sports activity has expanded. In this study, we will try to determine the role and importance of sports media in Algeria and the extent of its development of the professional sports experience in the field of football, and the possibility of keeping pace with all these transformations that professionalism will produce, whether on the economic, social, or even cultural and political levels. The commercial view of the future of professionalism places sports media in Algeria before great challenges, in terms of its ability to meet the various material and human needs to be able to cover the proceedings of the professional championship, especially in terms of providing news and information for the media, not to mention advertising and marketing, given their importance to clubs and teams from an economic standpoint, as well as the right of fans to know everything, big and small, related to their teams. The study we are about to conduct is based on research into the relationship of sports media, without which it is impossible to talk about sports professionalism and its development. In parallel with analyzing this relationship, we are trying to survey a sample of sports media journalists, as they are the actual practitioners of sports media in Algeria and are directly concerned with following the professional championship and meeting the media needs of the public.